Development And Training Of The Educational Leader - The Teacher – (Journal of Namibian Studies : History Politics Culture, 2023)
Teachers are considered important educational and social leaders within educational institutions. They serve as a role model for acquiring and learning various values, standards, and attitudes inside the classroom, providing organization, guidance, and direction to the learners. The teacher reflects cognitive, intellectual, and social responsibilities as an effective and significant leader within the educational system, being the primary responsible figure tostudents' families, who entrust them with shaping and educating their children.In order to achieve the educational and learning goals that benefit the individual, family, and society, it is essential to prioritize the teacher's pedagogical development and training. This involves effectively applying the theoretical knowledge acquired through practical field experiences to ensure a functional performance based on educational, social, and instructional leadership. By doing so, the teacher can contribute to the realization of educational objectives that serve the individual, the family, and the community.